Perbedaan Daya Tarik (Tensile Strength) dan Daya Terima Dodol Yang Dibuat Dari Tepung Rumput Laut Dan Bubur Rumput Laut - Choriah, Lela Juniar; , Rusdin Rauf, S.TP., M.P; , Eni Purwani, S.Si., M.Si (2015)
Introduction:Seaweed is one of the algae seaweed have a lot of benefits. One of them is a raw material of snack such as dodol.The tensile strength and acceptance level are the quality factors of dodol. The tensile strength is affected by gelatinization and retrogradation in dodol processing. Pulp or flour of seaweeds can be used as a raw material of dodol. Purpose : The purposeof the research was to investigate the difference in tensile strength and acceptance level of dodol manufactured from the powder dan pulp seaweeds. Method :The research was an experimental.Research design used wascompletely randomized design with two treatments, were flour and pulp seaweeds.Tensile strength data were analysed using one way anova, with significant level of 95 %.The acceptance level was tested using independent ttest . Result:The result indicated that there was no difference in tensile strength between dodol from flour and pulp of seaweeds. They were 0.57 N and 0.69 N, respectively.The acceptability test revealed that, the acceptance level of dodol made from seaweed flour was more than seaweed pulp, generally. Conclusion :There is no difference in tensile strength of dodol made from flour and pulp of seaweeds. In the acceptance test, however, there is a different between dodol made from flour seaweed and pulp seaweed. Keyword: seaweed, dodol, flour, pulp, tensile strength, acceptability. Reference:39 (1984-2013)